Philological Literacy Development Model: The Role Of Lecturers' Managerial Competency And Leadership Authority - Ulfah Rasyidatus Syarifah; Syamsul Anam; Asep Maulana (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This article aims to analyze and find the managerial competence of lecturers in constructing students' philological literacy awareness through poetry media at the Imam Syafi'i Islamic High School (STDI) in Jember Regency. This study uses a qualitative type with a descriptive exploratory approach. Data collection techniques include in-depth interviews, participatory observation, and documentation studies. The data is then analyzed through the stages of data reduction and data presentation, and conclusions are drawn using data validity, credibility, triangulation of methods and sources, and confirmability. Based on the results of the research findings, it is concluded that STDI Imam Syafi'i lecturers carry out their roles as authority holders who compile programs, organize language literacy teams, mobilize teaching staff and staff, optimize Campus resources, and control activities through monitoring activities of the process of activities and the achievement of philological literacy programs